The mediational role of motivation in the model of motor development in childhood: A longitudinal study. (May 2023) - Menescardi, Cristina; De Meester, An; Álvarez, Octavio; Castillo, Isabel; Haerens, Leen; Estevan, Isaac
Abstract: The aim of this study was twofold: first, to examine the stability of the hypothesized conceptual model of motor development (without and with including various types of motivation) when children are followed up one-year later, and second to examine longitudinally whether changes in one model variable predict changes in other variables, according to the hypothesized pathways in the model. A sample of 361 Spanish students (50.7% girls, 8–11 years old) voluntarily participated in this study. In relation to the first aim, structural equation modeling revealed the expected positive relationship between the model variables in both measurement times. That is: actual motor competence (MC) predicted physical activity (PA) ( p  < .001), perceived MC mediated the relationship between actual MC and PA ( p  < .001), and autonomous motivation mediated the relationship between perceived MC and PA ( p  < .05). Moreover, the comparison of the invariance analysis showed non-practical differences between the unconstrained model and the constrained model, supporting the stability of the model over time. In relation to the second aim, the hypothesized model in Time 2 controlling for Time 1 values showed that changes in children's actual MC positively predicted changes in their perceived MC ( p  < .001), which in turn, predicted changes in their autonomous motivation ( p  < .001), and PA ( p  < .001) at Time 2. Based on these findings Physical Education teachers are recommended to foster children's actual and perceived MC as well as their autonomous motivation over time in order to promote PA strategies for lifelong health. Highlights: This study offers longitudinal evidence of the relationships outlined in the model of motor development. The mediational role of children's autonomous motivation in the relation between their perceived motor competence and physical activity is evidenced over time. The inclusion of autonomous motivation in the model of motor development helps to explain a larger variance in children's physical activity.